Generalised trade-off model for energy efficient WSN synchronisation - Briff, P. (2015)
A mathematical framework to obtain a generalised energy-efficient trade-off model for generic wireless sensor networks (WSNs) while attaining sensing node synchronisation at a given network-wide estimation error threshold is presented. The model outputs both a theoretical optimal solution as well as a set of sub-optimal solutions to cater for real-worldWSNdesigns. The robustness of the proposed framework is examined with an example in which randomly deployed sensors are affected by path-loss and uncorrelated Rayleigh fading effects.